Efeito do plasma seminal interespécie na resposta inflamatória uterina de jumentas (Equus asinus) - Davanso, Luana de Santa [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Interesting production in the creation of hybrids using fresh semen from water has satisfactory pregnancy rates. However, when stallion semen is used to inseminate jennies, a significant reduction in conception rates is observed. The present study aimed to evaluate the effect of homologous and heterologous equine and donkey seminal plasma on sperm quality, post-mating uterine inflammatory response, and fertility in jennies. Donkeys and stallions were used, and semen was collected via artificial vagina and evaluated for concentration and motility. Seminal plasma was obtained by centrifugation, filtered, and stored for later use. In the in vitro experiment, ejaculates were fractionated and diluted (50 × 10⁶ spermatozoa/mL) into four treatments: control, semen without plasma, semen with homologous seminal plasma, and semen with heterologous seminal plasma. Samples were evaluated by CASA system and flow cytometry for motility and plasma and transverse membrane integrity. In the in vivo experiment, 18 jennies were distributed into experimental groups and inseminated with fresh semen adjusted to 2 × 10⁹ spermatozoa. Uterine inflammatory response was evaluated by endometrial cytology at 0, 6, 24, and 48 hours post-insemination, in addition to ultrasonographic evaluation of intrauterine fluid. Fertility was determined by embryo collection and gestational diagnosis. The different treatments did not significantly alter sperm quality, with conventional changes such as motility and rapid spermatozoa. However, plasma membrane integrity showed a higher index in horses (P<0.05). In donkeys, progressive motility showed greater stability over time (P<0.05). The uterine inflammatory response showed a similar pattern between the groups, but with significant alterations, with lower expression observed in group C2 compared to group J2 at the 48-hour time point (P<0.05). In vivo, donkeys showed higher pregnancy rates (P<0.05), and the use of donkey seminal plasma in equine semen suggested a beneficial effect on fertility. These results demonstrate that interspecific physiological differences influence sperm functionality and reproductive stages, showing the potential of donkey seminal plasma for optimizing interspecific crosses and hybrid production strategies.

A produção interespécies na criação de híbridos com sêmen fresco de jumentos em éguas tem taxas de gestação satisfatórias. No entanto, quando o sêmen de garanhões é utilizado para inseminar jumentas, verifica-se uma redução significativa nos índices de concepção. O presente estudo teve como objetivo avaliar o efeito do plasma seminal homólogo e heterólogo de equinos e asininos sobre a qualidade espermática, a resposta inflamatória uterina pós-cobertura e a fertilidade em jumentas. Foram utilizados jumentos e garanhões e o sêmen foi coletado por vagina artificial e avaliado quanto à concentração e motilidade. O plasma seminal foi obtido por centrifugação, filtrado e armazenado para posterior uso. No experimento in vitro, ejaculados foram fracionados e diluídos (50 × 10⁶ espermatozoides/mL) em quatro tratamentos: controle, sêmen sem plasma, sêmen com plasma seminal homólogo e sêmen com plasma seminal heterólogo. As amostras foram avaliadas por sistema CASA e citometria de fluxo quanto à motilidade e integridade de membrana plasmática e acrossômica. No experimento in vivo, 18 jumentas foram distribuídas em grupos experimentais e inseminadas com sêmen fresco ajustado a 2 × 10⁹ espermatozoides. A resposta inflamatória uterina foi avaliada por citologia endometrial nos tempos 0, 6, 24 e 48 horas pós-inseminação, além da avaliação ultrassonográfica de fluido intrauterino. A fertilidade foi determinada por coleta embrionária e diagnóstico gestacional. Os diferentes tratamentos não alteraram significativamente parâmetros convencionais de qualidade espermática, como motilidade e espermatozoides rápidos. Entretanto, a integridade da membrana plasmática apresentou maior índice em equinos (P<0,05). Nos asininos, a motilidade progressiva mostrou maior estabilidade ao longo do tempo (P<0,05). A resposta inflamatória uterina apresentou padrão semelhante entre os grupos, porém com alterações significativas, sendo observada menor expressão no grupo C2 em comparação ao grupo J2 no momento de 48 horas (P<0,05). In vivo, os asininos apresentaram taxas de prenhez superiores (P<0,05), e o uso de plasma seminal asinino em sêmen equino sugeriu efeito benéfico sobre a fertilidade. Esses resultados evidenciam que diferenças fisiológicas interespecíficas influenciam a funcionalidade espermática e os desfechos reprodutivos, indicando o potencial do plasma seminal de jumento para otimizar cruzamentos interespecíficos e estratégias de produção de híbridos.
Effect of interspecies seminal plasma on the uterine inflammatory response (Equus asinus)
Keywords: Asininos; Endometrite; Fertilidade; Fertility; Endometritis; Fertility